Socioeconomic Impacts of COVID-19 in Kenya - Pape, Utz Johann (World Bank, Washington, DC, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic has had a strong impact on the livelihoods of Kenyan households, even though employment and income levels are recovering. The second lockdown resulted in another surge in food insecurity. While access to education worsened again due to renewed school closures, health services remained widely accessible to the population. Kenyans are well informed about the preventive measures to avoid COVID-19 infections, and compliance with hygiene measures against the virus increased again during the second lockdown. The majority of Kenyans will be willing to take a COVID-19 vaccine, but many are concerned about potential side effects. One-half of the Kenyan population is anxious due to the fear of contracting COVID-19 and potential employment losses. This brief summarizes the key results of the Kenya COVID-19 rapid response phone survey (RRPS) tracking the socioeconomic impacts of the crisis from May 2020 to June 2021.